2012
DOI: 10.1021/jp209494z
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Boron-Doped Single Wall Carbon Nanotubes

Abstract: We have synthesized boron-doped single wall carbon nanotubes in a high vacuum chemical vapor deposition (CVD) system using a new boron precursor. Transmission electron microscopy was used in order to confirm the presence of single wall carbon nanotubes and field emission scanning electron microscopy to allow a qualitative characterization of the produced tubes. To estimate the doping level, we compared the Raman spectra with pure single wall carbon nanotubes and we found an upshifted G band as an evidence of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 32 publications
5
29
0
1
Order By: Relevance
“…Modification of CNTs has thus led to the creation of new functional and construction materials. 11 Doping of the carbonaceous materials with non-carbon atoms, such as nitrogen, [12][13][14][15][16][17][18][19] boron, [20][21][22][23][24] sulphur, [25][26][27][28][29] oxygen [30][31][32][33][34][35][36] and halogens 11,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] has been explored over the past two decades. Modification of the carbon surface and electronic properties has also been explored but the effect of chlorine (Cl) on the morphology of carbon nanomaterials is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…Modification of CNTs has thus led to the creation of new functional and construction materials. 11 Doping of the carbonaceous materials with non-carbon atoms, such as nitrogen, [12][13][14][15][16][17][18][19] boron, [20][21][22][23][24] sulphur, [25][26][27][28][29] oxygen [30][31][32][33][34][35][36] and halogens 11,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] has been explored over the past two decades. Modification of the carbon surface and electronic properties has also been explored but the effect of chlorine (Cl) on the morphology of carbon nanomaterials is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…The peak at 187.5 eV is associated with B 4 C [30], while the two peaks corresponding to higher binding energies are assigned to BCO 2 at 191.5 eV [30], respectively, which can be formed when boron atoms adopt a low-coordination substitutional site close to the graphene edges [19,20]. The peak at 190.7 eV is assigned to BC 2 O compound in the sample grown at 200 mTorr [29]. In Table 1, the amounts of boron present in the samples grown using Cu substrate exposed at 25, 75, and 200 mTorr pressure of triisopropyl borate vapor at 1000 ∘ C for 5 minutes are reported.…”
Section: Resultsmentioning
confidence: 97%
“…Few theoretical studies have been reported in the literature. Based on DFT calculations, a value between 188.5 and 190 eV for the binding energy is attributed in the XPS B 1s core-level spectra revealing the boron incorporation into substitutional sites [29]. High-energy resolution XPS measurements on boron-doped graphene have associated the peak with a binding energy of 189.6 eV to substitutional doping of graphene by boron atoms [20].…”
Section: Resultsmentioning
confidence: 99%
“…However, many boron carbon materials and boron doped carbon nanotubes have been successfully synthesized and reported. 44,[48][49][50] So that the nanotubes in this study could in principle be synthesized, especially for B 2 CNT(0, n) based on their low strain energies.…”
Section: Resultsmentioning
confidence: 99%